Penerapan Pendidikan Kristen Terhadap Kecerdasan Moral Anak Usia 5-6 Tahun Di Paud SOS HKBP Sitabotabo - Saniyanti Harefa; Uranus Zamili; Winarti Agustina (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2023)
The aim of this research is to apply Christian education to the moral intelligence of children aged 5-6 years at PAUD SOS HKBP Sitabobo. This research uses a descriptive qualitative approach. The data sources in this research are school principals and teaching staff. The data collection techniques used in this research are observation, documentation and interviews. And then the data analysis technique is carried out in three stages, namely data reduction, data presentation, and drawing conclusions. The results of this research indicate that there is an instillation of moral values ​​and Christian values ​​carried out by teachers in children aged 5-6 years at PAUD SOS HKBP Sitabota, starting from daily habits such as disciplinary time, greetings and greetings, teaching respecting each other's differences of opinion, teaching each other to love each other, teaching politeness to parents and other people, teaching an attitude of helping each other, and teaching children how to worship well, pray, sing and introduce themselves to God's creation. And when the teacher introduces good manners, or a helpful attitude, the teacher not only gives advice or orders, but also concrete examples. From the habits that teachers have taught to children, researchers see that not all children obey the rules or habits that have been taught by their teachers. And researchers also see that children are slowly starting to follow the rules or habits taught by their teachers at every meeting or every day. So the results of the research show that the morals of children at PAUD SOS HKBP Sitabobo have developed a lot.